ANALYSIS OF DIFFICULTY LEVEL AND DIFFERENT POWER OF PROBLEMS IN CLASS VIII SOCIAL STUDIES SMP NEGERI 1 KLUET UTARA - MuhasBaili; Akmaluddin; Siti Mayang Sari; Mhd. Syafii (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
The research entitled